Institutional memories and identities: words from Balseiro and de Gaviola. A legacy from Argentine physicists to future generations (Praxis Educativa, 2012)
This paper intends to be a brief tribute to two scientists of our country. Ongoing research (Director: Marcela Icko-wicz, MA; Advisor: Professor UBA Lidia M Fernandez): “Training and socialization processes and dynamics in the Comahue: a university case of groups of aca-demic excellence”, led me to carry out research, among other issues –on the history of science in our country and especially in Bariloche as a scientific foundation. Among the numerous scientific institutions which converge on Bariloche, we seek to vindicate the role in history of the CNEA and Instituto Balseiro. We have chosen these institutions in honour of José Antonio Balseiro and Enrique Ga-viola intending to revive their speeches, actions and achievements and as a means of contributing to the debate about the identity of Argentine scientists.
Keywords: generational transmission; memory; identity; scientific institutions; heritage